Job satisfaction among psychiatric nurses in Shafa hospital in Rasht - mahin nadem; naeima khodadadi; hasan ramzani; seyed moohamad javad muosavi (Journal of Holistic Nursing and Midwifery)
Introduction: Job environment as a second home of every individual should satisfy his mental ‎and spiritual needs. Among different jobs, nursing is an important and key job, because as ‎nurses job satisfaction increases, it can improve the quality of care given to patients and ‎increase their satisfaction.‎